Managing Better Net Working Capital With Data Assumption from Financial Statements in Manufacturing And Energy Companies- case in Emerging Markets Including Vietnam - HANH, HOANG THANH (The journal of contemporary issues in business and government, 2021)
In emerging markets in Asia including Vietnam, environment protection has been becoming meaningful in the context of global warming. There area huge number of used tires in region every year; so, pyrolysis firms have updated new technology to solve this environmental issue. That’s why it is important for us to consider solutions for better management of net working capital (including inventory for waste tires, for output products such as fuel oil, carbon black, steel). with all data collected from financial statements of energy firms. From financial reports on current business operation, we can make assumptions for input data of working capital. Hence, This paper will use statistic methods, together with practical experience in an energy firm case in one of developing countries in Asia, Vietnam. Finally, we think it is important to suggest some plans for better management of net working capital in this renewable energy business sector. This is a vital part of financial management mission in the business and in functions of CFOs and financial accounting team. JEL classification numbers: G00, G390